1999
DOI: 10.1046/j.1523-1747.1999.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory and Cytotoxic Effects of a Nitric Oxide Releasing Cream on Normal Skin

Abstract: We describe the pro-inflammatory and cytotoxic effects of nitric oxide in vivo in human skin. Nitrite and ascorbic acid were mixed on the skin of 12 normal volunteers, three times daily, to release nitric oxide. Exposure to nitric oxide was varied by randomizing the concentration of nitrite and duration of application. Nitric oxide treated skin showed significant increases in cells expressing CD3, CD4, CD8, CD68, neutrophil elastase, ICAM-1, VCAM-1, nitrosotyrosine, p53, and apoptotic cells compared with skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 44 publications
5
51
0
3
Order By: Relevance
“…In the present study there was a significant increase in apoptotic cells in the centrilobular and midzonal regions at 4 and 24 h ( Figure 1, Table 2), which confirmed a heterogenous spread of liver damage as previously reported (9). Positive ApopTag staining of the liver seen in Figure 1 may be indicative of cells undergoing repair or apoptosis (37), as the DNA is stained in the damaged nuclei of affected cells (38). In addition, significantly increased levels of ALT were seen at 4 and 24 h, indicating extensive liver damage caused by I/R injury.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study there was a significant increase in apoptotic cells in the centrilobular and midzonal regions at 4 and 24 h ( Figure 1, Table 2), which confirmed a heterogenous spread of liver damage as previously reported (9). Positive ApopTag staining of the liver seen in Figure 1 may be indicative of cells undergoing repair or apoptosis (37), as the DNA is stained in the damaged nuclei of affected cells (38). In addition, significantly increased levels of ALT were seen at 4 and 24 h, indicating extensive liver damage caused by I/R injury.…”
Section: Discussionsupporting
confidence: 90%
“…To confirm the heterogenic spread in the damage the harvested livers were histopathologically analyzed. ApopTag stained cells, staining DNA damaged nuclei, 47 were significantly increased in the centrilobular and midzonal regions, but not in the periportal region. Early ischemia reperfusion injury induces a burst of free radicals, 42 which in turn cause DNA strand breaks in the nuclei of the cells.…”
Section: Discussionmentioning
confidence: 84%
“…69 Again, it has been suggested that this effect may be partly because of the induction of apoptosis in infiltrating cells. In a human model similar to sunburn and psoriasis, Ormerod et al 68 described a cytotoxic effect of high concentrations of topically administered NO to immunocompetent cells, which was not seen with low concentrations. Aminoguanidine, an inhibitor of iNOS, prevented the impairment of renal vascular bed responses and reduced urine nitrate levels and apoptotic mononuclear cells in a rat model of experimental nephropathy.…”
Section: In Vivo Effects Of No and Its Therapeutic Potentialmentioning
confidence: 99%